Free Time as a Philosophical Category - B. J. Saidov (International Journal on Integrated Education, 2022)
In the article, the author discusses the time budget, the specifics of working and non-working time. Determines the place and value of free time in the time budget. Generalizes and analyzes the views of modern scientists about the structure of free time and ways to optimize it.